2013
DOI: 10.1002/prot.24349
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of key XRCC4/Ligase IV interfaces for targeted disruption of non-homologous end joining DNA repair

Abstract: Efficient DNA repair mechanisms frequently limit the effectiveness of chemotherapeutic agents that act through DNA damaging mechanisms. Consequently, proteins involved in DNA repair have increasingly become attractive targets of high-throughput screening initiatives to identify modulators of these pathways. Disruption of the XRCC4-Ligase IV interaction provides a novel means to efficiently halt repair of mammalian DNA double strand break repair; however; the extreme affinity of these proteins presents a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The minimal inhibitory fragment of the XRCC4-interacting region (XIR) capable of abolishing XRCC4/XIR complex was recently identified (181). The key interfaces of ligase IV necessary for interaction with XRCC4 were identified by the development a competitive displacement assay using ESI-MS/MS.…”
Section: Non-homologous End Joining and Chemotherapeutic Compounds Tamentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal inhibitory fragment of the XRCC4-interacting region (XIR) capable of abolishing XRCC4/XIR complex was recently identified (181). The key interfaces of ligase IV necessary for interaction with XRCC4 were identified by the development a competitive displacement assay using ESI-MS/MS.…”
Section: Non-homologous End Joining and Chemotherapeutic Compounds Tamentioning
confidence: 99%
“…The results suggest that by targeting the interface of helix 2 of DNA ligase IV, modulators that inhibit the XRCC4/DNA ligase IV complex may be identified. In addition, adjuvant compounds to further block the XRCC4/DNA ligase IV complex may be discovered by further targeting helix 1 and the loop regions of the helix–loop–helix clamp, which offer a secondary target surface (181). While this study has the potential to identify inhibitors of XRCC4, to date, inhibitors that have been tested in vivo and in clinical trials have not been described.…”
Section: Non-homologous End Joining and Chemotherapeutic Compounds Tamentioning
confidence: 99%
“…However, additional studies using ectopic expression of truncated Lig4 constructs have also shown that the sole BRCT2 domain was not sufficient to prevent formation of the endogenous XRCC4/Lig4 complex 16 . Moreover, a recent biophysical study with fragments from the XRCC4 Interacting Region (XIR) reported that a competitive displacement of the XIR from XRCC4 was only significant with either fragments of Lig4 containing Helix2 or with the Helix2 alone 26 . Accordingly, our MD simulation revealed that in addition to the BRCT2 domain, the small Lig4 Helix2 fragment had also several strong contacts while only Phe778 in Helix1 reached a percentage of contact over 80% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…XRCC4/Lig4 interface spans over ~2900 Å 2 16 . The XRCC4/Lig4 interaction resists high salt or urea 9 10 22 and organic solvents 26 . Indeed, the binding constant between the Lig4 XIR fragment and XRCC4 is in the nanomolar range 21 26 likely precluding disruption of the preformed complex by small molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation